LITERATURE FOR CHARACTER BUILDING: WHAT TO TEACH AND HOW ACCORDING TO RECENT RESEARCH - Ni Komang Arie Suwastini; Luh Putu Karina Febriyanti Aryawan; Ni Nyoman Artini; I Gusti Agung Sri Rwa Jayantini; Kadek Eva Krishna Adnyani (Undiksha Press, 2022)
Character building should be a priority in education, and this present study argues that literature can be a medium for developing students’ characters. This study employs George’s model of library research to synthesize arguments and results of previous studies on genres used in character education, the method used, the values identified in the literary texts used, and the challenges faced during the implementation of literature for building students' characters. The data sources are chosen from reputable international and accredited national journals, closely read, and synthesized to answer the research questions. It is revealed that the genres used by the previous studies for building character values are novels, short stories, children’s stories, films, poetry, folklores, and textbooks. The methods used are story-mediated storytelling, puppet-mediated storytelling, reading comprehension, literature-based instruction, and group discussion. The values identified as teachable through literature are religious, honest, tolerant, disciplined, hardworking, creative, autonomous, democratic, nationalism, patriotism, curious, appreciative, communicative, peace-loving, bibliophilic, environmental awareness, social awareness, and responsible. The challenges faced in using literature for character building are authentic material, time constraints, students' and teachers’ attitudes, proficiency, and critical thinking ability. Thus, the present study recommends using literature for building characters while urging teachers and researchers to find alternatives to cope with the challenges through continuous innovations and research.